Prevalensi dan Gambaran Kualitas Hidup Pasien Kusta di Kota Mataram - Sari Putu Suwita; Rika Hastuti Setyorini; Eva Triani; Dini Suryani; Rizka Vidya Lestari (Faculty of Medicine Universitas Mataram, 2022)
Background: Leprosy is a chronic infectious disease caused by the bacterium Mycobacterium leprae that attacks the peripheral nerves and can cause permanent deformity or disability. Leprosy can impact not only patient’s health, but also their quality of life. Currently there is no research on the quality of life of people with leprosy, especially in the city of Mataram. Method: This study is a cross-sectional study to determine the prevalence and the quality of life of leprosy patients in 2019-2020. Data on leprosy patients were obtained from all public health center in Mataram. Quality of life was assessed using the WHO questionnaire (WHOQoL-BREF) Results: In 2019-2020, there were 25 leprosy patients in the Mataram City area, equivalent to a prevalence of 0.00000504 or 0.5 cases per 10,000 population. 20 respondents were interviewed, with an average quality of life in the physical health domain of 57.32; psychology 59,79; social relations 59,58; and environment 57.81. Based on the quality-of-life category, 11 respondents (55%) belonged to the low score group in the physical and psychological health and 13 respondents (65%) belonged to the low group in the social and environmental relationship domain. Conclusion: The prevalence of leprosy in Mataram City in 2019-2020 was lower than the national prevalence in 2017. Some patients have a relatively low quality of life, especially in the domains of physical and psychological health and environmental relationships. Management of leprosy patients needs to pay attention to post-treatment management, especially related to leprosy disability.